2010
DOI: 10.1038/emboj.2009.395
|View full text |Cite
|
Sign up to set email alerts
|

Coordinated regulation of p53 apoptotic targets BAX and PUMA by SMAR1 through an identical MAR element

Abstract: How tumour suppressor p53 bifurcates cell cycle arrest and apoptosis and executes these distinct pathways is not clearly understood. We show that BAX and PUMA promoters harbour an identical MAR element and are transcriptional targets of SMAR1. On mild DNA damage, SMAR1 selectively represses BAX and PUMA through binding to the MAR independently of inducing p53 deacetylation through HDAC1. This generates an anti-apoptotic response leading to cell cycle arrest. Importantly, knockdown of SMAR1 induces apoptosis, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
76
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 60 publications
(80 citation statements)
references
References 35 publications
4
76
0
Order By: Relevance
“…12,35,36 A recent work suggested stress-dependent formation of a ternary complex of three proteins: p53, MDM2 and SMAR1, 37 another transcriptional target of p53 that can modulate p53 transactivation potential. 37,38 We now find that SMAR1, a predominantly nuclear protein becomes abundant in the cytoplasm under glucose deprivation. Thus glucose deprivation, a form of nutrient-depletion stress, can induce p53 IRESs and also increases cytoplasmic abundance of SMAR1 that in turn binds to p53 IRESs, indicating the role of SMAR1 in controlling translation of p53 isoforms.…”
mentioning
confidence: 70%
See 1 more Smart Citation
“…12,35,36 A recent work suggested stress-dependent formation of a ternary complex of three proteins: p53, MDM2 and SMAR1, 37 another transcriptional target of p53 that can modulate p53 transactivation potential. 37,38 We now find that SMAR1, a predominantly nuclear protein becomes abundant in the cytoplasm under glucose deprivation. Thus glucose deprivation, a form of nutrient-depletion stress, can induce p53 IRESs and also increases cytoplasmic abundance of SMAR1 that in turn binds to p53 IRESs, indicating the role of SMAR1 in controlling translation of p53 isoforms.…”
mentioning
confidence: 70%
“…49 SMAR1 has been implicated in maintaining cellular homeostasis and is a global regulator/modulator of gene expression. 37,38,[50][51][52][53][54] Our recent study showed that SMAR1 is directly linked to translation of both p53 and Δ40p53 in normal as well as glucose-deprived conditions.14-3-3σ was demonstrated as a preferential transcriptional target of Δ40p53. 5,14 The downstream effects of Δ40p53 induction on target gene activation, and the resulting biological outcome, have been previously explored.…”
Section: Discussionmentioning
confidence: 94%
“…Severe DNA damage results in sequestration of SMAR1, p53 acetylation and transactivation of Bax and Puma leading to apoptosis. Thus, sequestration of SMAR1 into the PML-NBs acts as a molecular switch to p53-dependent cell arrest and apoptosis in response to DNA damage (Sinha et al, 2010). The mechanisms by which moderate damage resulting from mild stress leads to repair, while severe damage results in the 'decision' to kill a cell, remains unclear.…”
Section: Cell Fate Decisionmentioning
confidence: 99%
“…A mild DNA damage induces SMAR1-generated anti-apoptotic response by promoting p53 deacetylation and specifically repressing Bax and Puma expression. Reducing the expression of SMAR1 by shRNA leads to significant increase in p53-dependent apoptosis (Sinha et al, 2010). Severe DNA damage results in sequestration of SMAR1, p53 acetylation and transactivation of Bax and Puma leading to apoptosis.…”
Section: Cell Fate Decisionmentioning
confidence: 99%
See 1 more Smart Citation